A ternary nanocomposite electrode of polyoxometalate/carbon nanotubes/gold nanoparticles for electrochemical detection of hydrogen peroxide. Issue 3 (28th November 2014) - Guo, Shuyue; Xu, Lin; Xu, Bingbing; Sun, Zhixia; Wang, Lihao
Abstract : In this work, a nanocomposite film electrode containing polyoxometalate (POM) clusters K6 P2 W18 O62 (P2 W18 ), carbon nanotubes (CNTs) and Au nanoparticles (AuNPs) was fabricated by a layer-by-layer self-assembly technique. Abstract : In this work, a nanocomposite film electrode containing polyoxometalate (POM) clusters K6 P2 W18 O62 (P2 W18 ), carbon nanotubes (CNTs) and Au nanoparticles (AuNPs) was fabricated by a smart combination of layer-by-layer (LbL) with the self-assembly technique. The synergistic effect of POM, CNTs and AuNPs on the electrocatalysis of H2 O2 was investigated to improve the sensitivity of H2 O2 detection. The response of (P2 W18 /CNTs/P2 W18 /AuNPs)4 electrodes to H2 O2 was remarkably enhanced due to large active sites and good electron conducting ability. The sensor exhibited a quick response (less than 1 second) to H2 O2 with a high sensitivity (596.1 μAm M −1 cm −2 ), and a low detection limit (52 nM). Based on the respective advantages of POMs, CNTs and AuNPs, the nanocomposite multilayer POMs/CNTs/POMs/AuNPs will have special properties and high potential for application.